Performance of Barley (Hordeum Vulgare L.) genotypes for growth yield and yield attributing traits in Prayagraj region - R. Ganesh; Prashant Kumar Rai (Annals of Agricultural Research, 2024)
The research titled “Performance of Barley (Hordeum vulgare L.) Genotypes for Growth Yield and Yield Attributing Traits in Prayagraj Region” was carried out during the Rabi season of 2023-24 at SHUATS, Prayagraj, under the Central Experimentation Research of the Department of Genetics and Plant Breeding. The goal was to identify the top-performing barley genotypes and assess genetic variability, heritability, genetic advance. The study evaluated 21 barley genotypes, including one control variety, across 22 quantitative traits including germination percentage, plant height at different stages, lodging percentage, flag leaf dimensions, spike length, peduncle length, awn length, number of tillers, canopy temperature at various stages, days to heading and maturity, spikelets per spike, grains per spike, grain yield per plant and per plot, test weight, and biomass. The results revealed significant variation among the barley genotypes for all traits studied. Six-row barley genotypes showed superior performance compared to two-row genotypes in terms of yield. Specifically, the genotype IBT-53 had the highest yield per plot at 208.73 g, surpassing the check variety IBT-80, which yielded 156.5 g per plot. High PCV and GCV recorded in Lodging percentage. germination percentage recorded under heritability. This research offers valuable insights into genotype performance and enhances the understanding of genetic and agronomic traits in barley cultivation.